Synthesis and structure‐activity relationship of mitochondria‐targeting peptoids with varying hydrophobicity and cationic charge. Issue 4 (14th July 2021) - Kim, Soyoung; Lee, Ji‐Yu; Choi, Jieun; Nam, Ho Yeon; Seo, Jiwon; Lee, Jiyoun
Abstract: Mitochondria‐targeted delivery methods offer a straightforward approach for studying mitochondria‐related diseases and potentially streamlining therapeutic development. Peptoids (oligo‐ N ‐substituted glycines) are biocompatible peptidomimetics that display similar physicochemical properties as peptides with the added advantage of enhanced resistance to proteolytic cleavage. In particular, amphipathic peptoids are membrane‐permeable and their cationic charges and hydrophobicity can be readily modified for specific purposes, such as cell penetration, anti‐cancer or antibacterial activity. Previously, we identified a series of amphipathic peptoids that showed efficient cell penetration and mitochondrial localization. As a continued effort to identify selective mitochondrial transporters, we designed new analogs with varying hydrophobicity and net charges. We observed that overall increase in hydrophobicity did not result in enhanced mitochondrial localization while maintaining high cell permeability. Moreover, a certain degree of a positive net charge was critical for mitochondrial localization. In conclusion, our mitochondria‐targeting peptoids provide a highly selective and robust delivery system for bioactive molecules. Abstract :